Communication Strategies of Digital Communities in Managing Opinion Polarization within Online Discussion Spaces - Yuzril Fadhil Muhammad; Farida Farida (PT FORMOSA CENDEKIA GLOBAL, 2026)
Online opinion polarization threatens the quality of public communication, yet the role of internal community communication remains underexplored. This qualitative case study uses digital netnography to examine how a WhatsApp-based RT/RW community in Surabaya manages polarization through informal moderation and shared communication norms. Data from observations, discussions, interviews with 10 informants, and document review were thematically analyzed. The findings show that informal moderation, calming message framing, and reinforcement of collective norms effectively reduce conflict and sustain dialogue. The study highlights the social capacity of digital communities to manage polarization constructively and contributes to theories of community-based digital communication governance and inclusive online dialogue strategies.